Control and stability on chaotic convection in porous media with time delayed fractional orders - Khaled Moaddy (Advances in Difference Equations, 2017)
Abstract In this paper, we study the effect of time delay and the scaled Rayleigh number on chaotic convection in porous media with fractional order. The stability analysis for different fractional-order cases is investigated and the effective chaotic range of the fractional order is determined by a general synchronization of nonidentical chaotic systems based on the active control technique. The numerical results demonstrate that the effect of various values of the scaled Rayleigh number R, time delay and fractional orders changes the chaotic convection behavior to limit cycles or stable system in porous media.